2019
DOI: 10.7554/elife.43204
|View full text |Cite
|
Sign up to set email alerts
|

The cryo-EM structure of a 12-subunit variant of RNA polymerase I reveals dissociation of the A49-A34.5 heterodimer and rearrangement of subunit A12.2

Abstract: RNA polymerase (Pol) I is a 14-subunit enzyme that solely transcribes pre-ribosomal RNA. Cryo-electron microscopy (EM) structures of Pol I initiation and elongation complexes have given first insights into the molecular mechanisms of Pol I transcription. Here, we present cryo-EM structures of yeast Pol I elongation complexes (ECs) bound to the nucleotide analog GMPCPP at 3.2 to 3.4 Å resolution that provide additional insight into the functional interplay between the Pol I-specific transcription-like factors A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…The Cterminal domain of subunit A12.2 shows only residual density in funnel domain of subunit A190 ( Supplementary Fig. 2b), but is not localized on the A135 lobe as observed in a 12-subunit EC 43 . Our eiPIC reconstruction shows strong density for the A49/A34.5 dimerization and A34.5 C-terminal tail domains ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The Cterminal domain of subunit A12.2 shows only residual density in funnel domain of subunit A190 ( Supplementary Fig. 2b), but is not localized on the A135 lobe as observed in a 12-subunit EC 43 . Our eiPIC reconstruction shows strong density for the A49/A34.5 dimerization and A34.5 C-terminal tail domains ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Recently, structural analysis of Rpa49CT provided further insights (16,29,41,(57)(58)(59)(60). These results, in combination with genetic data, indicated that the Rpa49 linker together with the Rpa49 tWH domain might stabilize the closed conformation of DNA-bound Pol I, thereby maintaining a narrow cleft (61,62). It is possible that an enzyme containing Rpa49LCT, but no Rpa34.5/Rpa49NT may not enter a locked state with a 3´ RNA displaced from the active center, and, thus, supports high processivity.…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, a dynamic position of Rpa12.2CT in the funnel of subunit Rpa190 depends on the transcriptional status of the elongating Pol I and might be a prerequisite to overcome transcriptional barriers (19,20,26,29,29,41,57,60,71,72). Furthermore, it was suggested that competition between Rpa12.2CT and the heterodimer Rpa34.5/Rpa49 for binding of the Pol I lobe might result in the reversible binding of the heterodimer which could contribute to modulate Pol I activity (62). Such a dynamic interaction could also influence movement through nucleosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, structural analysis of Rpa49CT provided further insights [16,29,41,[57][58][59][60]. These results, in combination with genetic data, indicated that the Rpa49 linker together with the Rpa49 tWH domain might stabilize the closed conformation of DNA-bound Pol I, thereby maintaining a narrow cleft [61,62]. It is possible that an enzyme containing Rpa49LCT, but no Rpa34.5/Rpa49NT may not enter a locked state with a 3´ RNA displaced from the active center, and, thus, supports high processivity.…”
Section: Discussionmentioning
confidence: 99%